EVALUATION OF EDUCATION AND LEADERSHIP SUPERVISION HEADMASTER - Vinus FITRIATI; Istaryatiningtias ISTARYATININGTIAS; CH SUPRAPTO (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2021)
upervision of education is based on the principal, whose consideration must guarantee the purity and dynamics in the education system. To complete certain tasks, both simple and specific, it is required that the principal must start his activities, continue and complete the same thing by complying with the respective principles of the activity. Realizing the views and theories of education supervision in the education system, and getting the same assistance for improving the quality and production of a constant quality of new education depends on the basic principles of supervision. Educational guidelines must follow the principles of supervision and educational guidelines for improving the conditions of education and learning. They must always pay attention to these principles in their plans and activities. The principal must also have a leadership character that can motivate the school community to always do their job well. Thus, due to the importance of compliance and consideration of each principle in significant supervision and educational guidance, in this thesis, an attempt has been made to state the principles of supervision, which can guide supervisors in the design and implementation of education supervision.